Instrument Development “Intention to Stay Instrument” (ISI) - Kumar M., Dileep; Govindarajo, Normala S (Canadian Center of Science and Education, 2014)
Quite a few instruments exist in literature to measure the concepts like absenteeism, attrition, organizational member’s intention to leave and retention. While, there is always confusion between the variable’s and its appropriateness when contextualize the topic to various industries, sectors and regional applications. These variances evidently may observe when an instrument developed in the west and apply it in east to get its validity and reliability. In this context, an instrument developed to measure the causative factors of ‘member’s intention to stay’, especially focused on individual and organizational factors in the manufacturing sector. The instrument development process was initially followed the qualitative research method. Techniques like content analysis, personal interviews with the organizational members, focus group discussion and Delphi technique were adopted. After identification of the variables through Delphi, these variables were exposed to validity and reliability test. Further, content, construct and face validity was made on the sub factors and items generated in the instrument. The instrument was finalized with 76 items under 21 sub factors of ‘member’s intention to stay’.